Functional properties of Ganoderma lucidum extract: antimicrobial and antioxidant activities - TEHRANIAN, Mahdis Jamshidi; JOUKI, Mohammad; SHAKOURI, Mohammad Javad; JAFARI, Sara (Food Science and Technology, 2023)
This research was conducted to investigate the functional properties of Ganoderma lucidum extract. The antimicrobial activity was evaluated on some bacteria causing food spoilage like Staphylococcus aureus and Escherichia coli. Antioxidant activity was investigated by examining the effect of the extract on DPPH and ABTS free radicals, determining the amount of total phenolic compounds and flavonoids. Based on the results, the antimicrobial and antioxidant activities of the extract were increased by increasing the concentration. Staphylococcus aureus showed the highest sensitivity to Ganoderma extract with minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of 50 and 100 μg/mL, respectively. The total phenols amount was equal to 383.727 milligrams of gallic acid equivalent per gram (mg GAE/g) of the extract and the total flavonoid was equal to 28.047 milligrams of quercetin equivalents per gram (mg QE/g) of extract. The results of antioxidant activity tests showed that the concentration of 400 μg/mL had the highest scavenging activity of 85.9 and 90.12% for DPPH and ABTS free radicals, respectively. Therefore, considering the potential antioxidant activity and the rich amounts of phenolic compounds in Ganoderma extract, it can be used in the pharmaceutical and food industries instead of synthetic antioxidants and other chemical preservatives to delay lipid peroxidation and prevent the growth of food pathogens.